Pengaruh pemberian ubi jalar ungu (Ipomoea batatas L.Poir) terhadap kadar superoksida dismutase (SOD) tikus wistar jantan (Rattus Norvegicus) yang dipapar asap rokok - Widyanti, Alfreda Sabrina; Ardiaria, Martha; Widyastuti, Nurmasari (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: Cigarette smoke exposure is one of the source of free radicals that causes oxidative stress and decreases superoxide dismutase (SOD) level. Purple fleshed sweet potato is a type of food that contains antioxidants to neutralize oxidative stress.Objectives: To study the effect of purple fleshed sweet potato on superoxide dismutase (sod) level on rats exposed to cigarette smoke.Methods: This was a true experimental study with a post-test randomized control group design. The rats were randomized into 4 groups (6 rats in each group). The negative control group (K-) was treated with standard diet; the positive control group (K+) was treated with cigarette smoke exposure and standard diet; the treatment 1 (P1) group was treated with standard diet and purple fleshed sweet potato with the dose of 8 g / 200 g bw/day, and the treatment 2 (P2) group was treated with cigarette smoke exposure and purple fleshed sweet potato with the dose of 8 g /200 g bw/day.Results: There was a significant difference of SOD levels in each group (p=0.00) except between group K- and P1. Giving purple fleshed sweet potatoes increased SOD levels as much as 85.81±4.59 (P1). The K+ group had the lowest SOD level 22.34±3.98. The SOD level for K- group and P2 group was 82.27±4.59 and 67.73±6.68 respectively.Conclusion: The highest SOD level is on the treatment 1 group which is administered with purple fleshed sweet potato.